SISTEM PERANCANGAN PERUNDANG - UNDANGAN DI INDONESIA DAN METODE OMNIBUS LAW: BERDASARKAN HUKUM KENEGARAAN - Leonardy Julio Tanjaya; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
Law is a system of rules thats been created and enforced through government to maintain everyindividual in the Country, This Research was aimed to examine the system that Indonesia have toestablished Law in Indonesia. Indonesia have their own Political Framework that separate eachinstitution on what their Rights and Obligation. In which in Indonesia Government Institution thathave the Rights and Obligation on making the first concepts until the Law become Legitimate Law isDPR (Dewan Perwakilan Rakyat), The President, and DPD (Dewan Perwakilan Daerah) that have theRights to discuss or suggest on making an Law in Indonesia. In this Research is also aimed on to knowevery procedure that need to do such as any conference or meetings that every Government Instituitionthat have the Rights on making the Law, How many Conference that need to do, even on whatProcedure thats need to takes if the Meetings between each Goverments Instituition have made aresult. With Omnibus Bill or Omnibus Law Job Creation as one of the example.